Expression And Characterization Of A Recombinant Superoxide Dismutase From Lactococcus Lactis M4 - Tan, Boon Hooi (2009)

(untitled)
Lactococcus lactis is widely used in the dairy industry for the production of fermented food. During industrial process, L. lactis is often exposed to various environmental stresses such as oxidative stress. Superoxide dismutase (SOD) plays an important role in protecting living organisms from oxidative stress by catalyzing the dismutation of superoxide radical to oxygen and hydrogen peroxide. Hence, it is essential to study the SOD from L. lactis in details. A full-length superoxide dismutase gene (sod) was amplified from a locally isolated Lactococcus lactis M4 strain by polymerase chain reaction (PCR). The gene was first cloned in pCR®-BluntII-TOPO® vector and then subcloned into pRSET A expresion vector. The construct was transformed into Escherichia coli strain BL21(DE3)pLysS for protein expression. Restriction enzyme digestion of the construct indicated the presence of the sod gene. BLASTN analysis showed the DNA sequence of the query gene was 98% homologous to the published sodA nucleotide sequence of L. lactis subsp. lactis IL1403. This SOD gene composed of 621 nucleotides that could encode a protein of 206 amino acids. It was predicted to be a manganese-SOD (MnSOD) based on homology comparison with amino acid sequences of MnSOD from other organisms. Expression of the recombinant protein was induced by isopropyl-β-D-thiogalactopyranoside. The recombinant superoxide dismutase was purified to homogeneity by immobilised ion affinity chromatography and gel filtration chromatography. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and western blot analysis showed that the recombinant SOD had a molecular mass of approximately 27 kDa. However, the molecular mass of native enzyme was estimated to be 114.8 kDa by gel filtration chromatography, implying that the recombinant SOD is a tetramer. The purified recombinant enzyme had a pI of 4.5, exhibited maximal activity at 25°C and pH 7.2, respectively. It was also thermostable up to 45°C. SOD activity was inhibited by sodium azide, ethylene diamine tetracetic acid and sodium dodecyl sulphate. The insensitivity of this recombinant SOD to cyanide and hydrogen peroxide confirmed that it was a MnSOD. In conclusion, a gene coding for MnSOD in L. lactis M4 was cloned and expressed in E. coli as an active enzyme. The expressed recombinant MnSOD was purified to homogeneity and characterized.